THE ROLE OF INVESTMENT AND PREFERENTIAL LOANS IN THE DEVELOPMENT OF SMALL BUSINESS ENTITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this scientific article, small business and private entrepreneurship in our country is an important factor in the development of the economy, increasing the employment and income of the population, and in this regard, the preferential loans created for business activities and their importance are discussed.